2016
DOI: 10.1111/jfb.13024
|View full text |Cite
|
Sign up to set email alerts
|

Estimating tissue‐specific discrimination factors and turnover rates of stable isotopes of nitrogen and carbon in the smallnose fanskateSympterygia bonapartii(Rajidae)

Abstract: This study aimed to estimate trophic discrimination factors (TDFs) and metabolic turnover rates of nitrogen and carbon stable isotopes in blood and muscle of the smallnose fanskate Sympterygia bonapartii by feeding six adult individuals, maintained in captivity, with a constant diet for 365 days. TDFs were estimated as the difference between δ(13) C or δ(15) N values of the food and the tissues of S. bonapartii after they had reached equilibrium with their diet. The duration of the experiment was enough to rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 58 publications
(91 reference statements)
0
15
0
Order By: Relevance
“…First, by the time of sampling at the end of the experiment, control individuals had been on a constant diet for 1250 days and had not exhibited substantial, directional change in bulk tissue δ 13 C or δ 15 N values for >400 days (Kim et al 2012a). Second, a recent review found that the longest time interval reported for elasmobranch muscle to replace 95% of endogenous carbon or nitrogen was 422 days (Galván et al 2016). Although we propose that the appearance of steady states may not always be reliable (as described in the previous section), the fact that control sharks consumed the same diet for a period three times longer than the maximum reported interval for 95% turnover makes it likely that they had reached a steady state.…”
Section: Discussionmentioning
confidence: 99%
“…First, by the time of sampling at the end of the experiment, control individuals had been on a constant diet for 1250 days and had not exhibited substantial, directional change in bulk tissue δ 13 C or δ 15 N values for >400 days (Kim et al 2012a). Second, a recent review found that the longest time interval reported for elasmobranch muscle to replace 95% of endogenous carbon or nitrogen was 422 days (Galván et al 2016). Although we propose that the appearance of steady states may not always be reliable (as described in the previous section), the fact that control sharks consumed the same diet for a period three times longer than the maximum reported interval for 95% turnover makes it likely that they had reached a steady state.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis was tested using Baltic mysids Neomysis integer (Crustacea, Mysidacea) fed an isotopically uniform diet under laboratory conditions and analysing mysid individual growth and stable isotope signature in concert. Another concern in intrapopulation variability analysis is the sex‐related effects on isotope fractionation due to possible differences in resource allocation to somatic growth and maturation observed in a variety of species (Galván, Jañez, & Irigoyen, ; Gratton & Forbes, ; Kurle, Koch, Tershy, & Croll, ). To estimate these effects, sex of the test animals was included as a covariable in the data analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Another concern in intrapopulation variability analysis is the sexrelated effects on isotope fractionation due to possible differences in resource allocation to somatic growth and maturation observed in a variety of species (Galván, Jañez, & Irigoyen, 2016;Gratton & Forbes, 2006;Kurle, Koch, Tershy, & Croll, 2014). To estimate these effects, sex of the test animals was included as a covariable in the data analysis.…”
mentioning
confidence: 99%
“…where TL δ 15 N is the trophic position of the predator, TLbaseline is the trophic position of the baseline (TLbaseline = 2), δ 15 Npredator is the δ 15 N value of the consumer, δ 15 Nbaseline is the δ 15 N value of the baseline and 1.5‰ is the expected enrichment in δ 15 N per trophic level. The enrichment constant of δ 15 N used was based on a study by Galván et al (2016), which estimated the trophic discrimination factors (TDF) and turnover rates in blood and muscle of the small nose fanskate Sympterygia bonapartii (Müller & Henle, 1841) through controlled feeding. The results found by Galván et al (2016) led to an estimated TDF value for S. bonapartii of 1.5‰.…”
Section: Trophic Level Estimatementioning
confidence: 99%
“…The enrichment constant of δ 15 N used was based on a study by Galván et al (2016), which estimated the trophic discrimination factors (TDF) and turnover rates in blood and muscle of the small nose fanskate Sympterygia bonapartii (Müller & Henle, 1841) through controlled feeding. The results found by Galván et al (2016) led to an estimated TDF value for S. bonapartii of 1.5‰. Since the enrichment constant may vary according to the species studied (Post, 2002;Hussey et al, 2014), the estimated value for S. bonapartii was used because it lives in a benthic habitat similar that of H. marianae.…”
Section: Trophic Level Estimatementioning
confidence: 99%